2013
DOI: 10.1016/j.chemgeo.2013.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Precambrian banded iron formation diagenesis

Abstract: Post-depositional diagenetic alteration makes the accurate interpretation of key precipitation processes in ancient sediments, such as Precambrian banded iron formations (BIFs), difficult. While microorganisms are proposed as key contributors to BIF deposition, the diagenetic transformation of precursor Fe(III) minerals associated with microbial biomass had not been experimentally tested. We incubated mixtures of ferrihydrite (proxy for biogenic ferric oxyhydroxide minerals) and glucose (proxy for microbial bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 95 publications
1
75
0
Order By: Relevance
“…Kennedy et al showed that pure ferrihydrite transformed to haematite at 80°C, whereas it remained stable when associated with bacteria at the same temperature 38 . Using experimental conditions similar to ours, Posth et al 29 demonstrated that, after 14 days at 170°C-120 MPa, ferrihydrite alone transformed to haematite while ferrihydrite associated with glucose completely transformed to haematite, magnetite and siderite 29 . Interestingly, biogenic ferrihydrite recovered at deep-sea hydrothermal vents was preserved after heating 20 min up to 400°C and transformed to haematite only at 500°C (ref.…”
Section: Discussionmentioning
confidence: 98%
“…Kennedy et al showed that pure ferrihydrite transformed to haematite at 80°C, whereas it remained stable when associated with bacteria at the same temperature 38 . Using experimental conditions similar to ours, Posth et al 29 demonstrated that, after 14 days at 170°C-120 MPa, ferrihydrite alone transformed to haematite while ferrihydrite associated with glucose completely transformed to haematite, magnetite and siderite 29 . Interestingly, biogenic ferrihydrite recovered at deep-sea hydrothermal vents was preserved after heating 20 min up to 400°C and transformed to haematite only at 500°C (ref.…”
Section: Discussionmentioning
confidence: 98%
“…Capsules were subjected for 14 days at 170¼C and 1.2 kbar, approximately the diagenetic pressure and temperature (P-T) conditions of one of the largest and most studied iron formations on Earth, the Transvaal Supergroup BIF (Miyano and Klein, 1984;Miyano, 1987). Furthermore, these conditions mimic previous diagenetic capsule experiments (Posth et al, 2013b;Kšhler et al, 2013), and therefore, facilitate a ready comparison between experimental conditions. Our experimental duration and P-T parameters are obviously much abbreviated compared to natural burial diagenesis and metamorphism that takes thousands to millions of years; and are less than experienced by some IF which were subjected to amphibolite facies.…”
Section: Simulated Diagenesis Experimentsmentioning
confidence: 99%
“…Diagenetic capsule experiments on synthetic Fe oxyhydroxide precipitates (Posth et al, 2013b) demonstrate that the Fe mineralogy observed in IF today can be reproduced after incubation of synthetic 2-line ferrihydrite in the presence or absence of glucose (as a proxy for biomass). Capsules were subjected for 14 days at 170¼C and 1.2 kbar, approximately the diagenetic pressure and temperature (P-T) conditions of one of the largest and most studied iron formations on Earth, the Transvaal Supergroup BIF (Miyano and Klein, 1984;Miyano, 1987).…”
Section: Simulated Diagenesis Experimentsmentioning
confidence: 99%
See 2 more Smart Citations